Smart Grain Dispenser with Officer Locking System - Barai, V; Balla, N; Khobragade, C; Mahajan, S; Maurya, Avinash (International Journal of Computer Sciences and Engineering, 2025)
Every Indian Family issued ration card based on which given subsidized food grains are distributed. For distribution and storing of food grains, an effective smart approach is proposed in this paper. Due to manual distribution sometimes the user does not get actually measured food grains as it gets replaced with a poor quality of food grains. The main purpose of designing the system is to provide security for grains which are received from the government by the interfacing officer locking system. The proposed design provides ease of use to the customers. The presented system is offline as a database of user and officer is stored in memory according to the particular areas. The authentication is provided for the officer who loads the grains in a container and for the customer to receive the grains. Interchanging of food grains is prohibited after proper verification of identification number.